A new perspective on selenium’s impact on renal function: European population-based analysis of plasma proteome-mediated Mendelian randomization study - Fu, Shaojie; Qian, Man; Yuan, Zishu; Su, Sensen; Ma, Fuzhe; Li, Fan; Xu, Zhonggao (Frontiers in Endocrinology, 2024)
The relationship between selenium and renal function has always attracted widespread attention. Increased selenium level has been found to cause impaired renal function in our previous study, but the mechanism is not clear. In this study, we evaluate the potential mediating effects of plasma proteome in the association of selenium level and renal function to understand the mechanisms of selenium's effect on renal function.Methods: Utilizing two-sample two-step mediating mendelian randomization (MR) methodology to investigate the genetically causal relationship between selenium level and renal function as well as the role of the plasma proteome in mediating them. Additionally, the mediating proteins were enriched and analyzed through bioinformatics to understand the potential mechanisms of selenium effects on renal function.In the MR analysis, an increase in selenium level was found to decrease estimated glomerular filtration rate (eGFR). Specifically, for each standard deviation (SD) increase in selenium levels, eGFR levels are reduced by 0.003 SD [Beta (95% CI): -0.003 (-0.004 ~ -0.001), P=0.001, with no observed heterogeneity and pleiotropy]. Through mediation analysis, 35 proteins have been determined mediating the genetically causal effects of selenium on the levels of eGFR, including Fibroblast growth factor receptor 4 (FGFR4), Fibulin-1, Cilia-and flagella-associated protein 45, Mothers against decapentaplegic homolog 2 (SMAD2), and E3 ubiquitin-protein ligase ZNRF3, and the mediation effect rates of these proteins ranged from 1.59% to 23.70%. In the enrichment analysis, 13 signal transduction pathways, including FGFR4 mutant receptor activation and Defective SLC5A5 causing thyroid dyshormonogenesis 1, were involved in the effect of selenium on eGFR levels.Our finding has revealed the underlying mechanism by which increased selenium level lead to deterioration of renal function, effectively guiding the prevention of chronic kidney disease and paving the way for future studies.